Nursing plans for prevention of sexually transmitted diseases - Farzanegan, Z. (Iran University of Medical Sciences, 1995)
Sexually transmitted diseases (STD) are a significant problem in Canada and have many personal and financial effects on the society. STDs are very prevalent in adults and adolescents who are very sexually active. Women are more affected by these diseases and after many years, appear in the shape of infertility, ectopic pregnancy, and cervical cancer. Majority of women never know about her infection but in many cases STDs are preventable with contraceptive methods and curable with antimicrobial drugs. Many documents have presented by national health and wellbeing section about guidelines for diagnosis and prevention of STDs in children and adults and finally reduction of prevalence of STDs and its effects.